A Review of Applications of the Advocacy Coalition Framework in Swedish Policy Processes. (December 2016) - Nohrstedt, Daniel; Olofsson, Kristin
Abstract : In recent decades, there has been a growing interest among public policy scholars to explore the applicability of policy process frameworks across political systems. One popular framework simplifying the complexity of public policy is the Advocacy Coalition Framework (ACF). Prior research suggests that the ACF is useful for identifying variables and relationships influencing the policy process but also that questions remain regarding its applicability in different political systems. This paper addresses some of these questions by conducting a review of empirical ACF applications in Sweden—a country where the ACF has received growing attention. We code 25 of the most complete applications across themes associated with advocacy coalitions, learning, and policy change. We also examine what research methods are employed, what comparisons are made between the ACF and other frameworks, and what modifications are suggested by scholars. The conclusion identifies strengths and limitations of the ACF in the context of the Swedish policy process and suggests directions for future research in Sweden and beyond.